DIGITAL VERSUS PRINT: AN EXPLORATION OF STUDENTS COMPREHENSION BASED ON READING TYPE - Basri, Muh. Bahly; Rapi, Muhammad; Sultan, Sultan; Ilham, Muhammad; Yasinta, Iin Nur (JURNAL NALAR PENDIDIKAN, 2024)
The PISA score in 2022 decreased by 12 points from the previous edition. This result is the lowest score on record and extends the downward trend in scores from the last five editions of the assessment. In reading tests, reading techniques and materials affect students' reading ability. This study aims to reveal the effect of reading materials and reading frequency on students' reading comprehension ability. Quantitative research was applied to 64 samples. The research data were collected using questionnaires and objective tests. The results showed that students who liked reading digital reading had better reading comprehension (mean rank: 36.58) than students who liked reading print (mean rank: 29.88). Based on the frequency of reading, students' interest in reading was classified as low: high (n= 1); medium (n= 15); and low (n= 48). Reading frequency was positively correlated with reading comprehension performance. High reading frequency has the best reading comprehension performance (mean rank: 62.00), medium frequency (mean rank: 38.33), and low frequency (mean rank: 30.06). Students' low interest in reading is a signal for interventions to develop students' interest in reading, which has implications for improving academic performance.